Efficacy of Early Physical Therapy for Different Birth Weight Infants and Assessment of Their Motor Skill Development - Margarita Senkutė; Ernesta Sendžikaitė; Alfonsas Vainoras (Lithuanian Sports University, 2018)
Research background and hypothesis. The survey was conducted to determine impact of physical therapy on different birth weight babies with specific motor development function delay and muscle spasticity. Our research hypothesis was that physical therapy would affect baby motor development regardless of their birth weight. Research aim. The aim of this study was to assess motor development of the infants with different birth weight before and after early physical therapy. Research method. Forty nine infants were assessed with Munich Functional Development Diagnostic Assessment during their first year of life. This scale helps to assess the basic motor functions: crawling, sitting, walking, grasping, language speech, perception and social development in the first months of infant life. Also, this method helps to identify potential problems and to give the infant the required support. The results were compared with the standard. Research results. The results indicated that the motor function (crawling, sitting, walking and grasping) of infants with very low and normal birth weight statistically significantly differed before physical therapy. Walking motor development differences for infants with very low and low birth weight were statistically significant (p  < 0.05). The results showed that after physical therapy there was no significant difference in the motor development of infants with very low and normal weight in crawling and sitting (p > 0.05). After physical therapy we noticed that there was no significant difference between walking and grasping development in babies with very low, low and normal weight (p > 0.05). Discussion and conclusions. Summarizing the results we suggest that specific motor development function delay and muscle spasticity in babies with different birth weight before physical therapy was significantly different in  such  motor  functions  as  crawling,  sitting,  walking  and  grasping  dependently  on  birth  weight. After  physical therapy, we also observed 80% of motor development improvement for very low birth weight, 45% development improvement for low birth weight, and 60% development improvement for normal weight infants. Keywords: spastic muscle, specific motor function development delay.